The method of the deformation operator in quantum acoustics – a formulation of perturbation calculus - PIEKARSKI, Sławomir (Archives of Acoustics, 1983)
This paper gives a formulation of perturbation calculus which is useful for the description of coherent states related to the propagation of ultrasonic waves in crystals. This formulation is based on the results of the theory of coherent states, particularly on the properties of the deformation operator. The method of the construction of the initial state, which is used in perturbation calculus, is verified through comparison with the results of the method of the quasi-equilibrium density matrix based on the use of information theory in statistical physics. The method of perturbation calculus which is presented in this paper describes the time dependence of the mean value of any physical quantity for a crystal which undergoes dynamic deformation. This method makes it possible to grasp the dependence of phenomena observed on the phase and amplitude of the initially excited acoustic wave.